Hydrogen Sulfide Attenuates High Glucose-Induced Human Retinal Pigment Epithelial Cell Inflammation by Inhibiting ROS Formation and NLRP3 Inflammasome Activation - Wang, Peng (Mediators Inflamm, 2019)
Hydrogen sulfide (H(2)S) has been shown to protect against oxidative stress injury and inflammation in various high glucose-induced insult models. However, it remains unknown whether H(2)S protects human retinal pigment epithelial cells (RPE cells) from high glucose-induced damage. In the current study, cell viability, proinflammatory cytokines, ROS, and inflammasome markers were compared in a low glucose- and high glucose-induced cell culture system. The antioxidant N-acetylcysteine (NAC), NLRP3 siRNA, and NaHS were used to test RPE cell responses. The results demonstrate that compared with the low-glucose culture, high glucose triggered higher cell death and increased IL-18 and IL-1β mRNA expression and protein production. Furthermore, high glucose increased the mRNA expression levels of NLRP3, ACS, and caspase-1. Notably, NAC, a ROS scavenger, could attenuate high glucose-induced ROS formation and IL-18 and IL-1β mRNA and protein expression and block inflammasome activation. Silencing the NLRP3 gene expression also abolished IL-18 and IL-1β mRNA and protein expression. Intrudingly, H(2)S could ameliorate high glucose-induced ROS formation, IL-18 and IL-1β expression, and inflammasome activation. Taken together, the findings of the present study have demonstrated that H(2)S protects cultured RPE cells from high glucose-induced damage through inhibiting ROS formation and NLRP3 inflammasome activation. It might suggest that H(2)S represents a potential therapeutic target for the treatment of diabetic retinopathy.